2016
DOI: 10.1103/physrevb.93.035306
|View full text |Cite
|
Sign up to set email alerts
|

Surface code architecture for donors and dots in silicon with imprecise and nonuniform qubit couplings

Abstract: A scaled quantum computer with donor spins in silicon would benefit from a viable semiconductor framework and a strong inherent decoupling of the qubits from the noisy environment. Coupling neighbouring spins via the natural exchange interaction according to current designs requires gate control structures with extremely small length scales. We present a silicon architecture where bismuth donors with long coherence times are coupled to electrons that can shuttle between adjacent quantum dots, thus relaxing the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 50 publications
3
102
0
1
Order By: Relevance
“…Based on this, they presented a multi-valley effective-mass theory (MV-EMT) by explicitly including the central-cell correction along with a non-static dielectric screening of the Coulomb potential representing the donor. Similar EMT based formalisms have been widely applied by various studies later on to investigate the physics of shallow donors [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, they presented a multi-valley effective-mass theory (MV-EMT) by explicitly including the central-cell correction along with a non-static dielectric screening of the Coulomb potential representing the donor. Similar EMT based formalisms have been widely applied by various studies later on to investigate the physics of shallow donors [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We choose this scope because it allows us to consider important near-term challenges for error correction using quantum dots; moreover, there are several proposals that provide good coverage of large-scale silicon-qubit designs in the longer term [1,2,5,[63][64][65][66]. Based on recent results in SiMOS dots [27,40,67], we design spin-control protocols and error-correction instruction sequences.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the rapid manipulation of two nearly degenerate qubits in a regime where coherence times can be long, even for natural silicon. This addressability is not only important for donor-dot quantum computing schemes like the one described by Pica et al 10 , but also for other quantum computing architectures relying on the use of more than two donor spin states.…”
Section: Figmentioning
confidence: 99%
“…By varying this polarization, we demonstrate the selective addressability of the 7.03 GHz clock transitions. This will be important for hybrid donor-dot quantum computing schemes since the 5 GHz clock transition was recently predicted to form an avoided crossing with silicon based quantum dots 10 . This was discussed in the donor-dot surface code proposal by Pica et al 10 which also suggested addressing the clock transitions using microwave polarization.…”
mentioning
confidence: 99%
See 1 more Smart Citation